Miniaturized liquid metal composite circuits with energy harvesting coils for battery-free bioelectronics and optogenetics - Rocha, Denis (2025)
Over the past years, rapid progress has been made on soft-matter electronics for wearable and implantable devices, for bioelectronics and optogenetics. Liquid Metal (LM) based electronics were especially popular, due to their long-term durability, when subject to repetitive strain cycles. However, one major limitation has been the need for tethering bioelectronics circuits to external power, or the use of rigid bulky batteries. This has motivated a growing interest in wireless energy transfer, which demands circuit miniaturization. However, miniaturization of LM circuits is challenging due to low LM-substrate adhesion, LM smearing, and challenges on microchip-interfacing. In this article, we address these challenges by high-resolution laser-assisted micropatterning of biphasic LM composites and vapor-assisted LM microchip soldering. Through development of a search algorithm for optimization of the biphasic ink coil performance, we designed and implemented micro coils with trace spacing of 50 μm that can harvest a significant amount of energy (178 mW/cm2) through near field inductive coupling. We show miniaturized soft-matter circuits with integrated SMD chips such as NFC chips, capacitors, and LEDs that are implemented in a few minutes through laser patterning, and vaporassisted soldering. In the context of optogenetics, where lightweight, miniaturized systems are needed to provide optical stimulation, soft coils stand out in terms of their improved conformability and flexibility. Thus, this article explores the applications of soft coils in wearable and implantable devices, with a specific focus on their use in optogenetics.